Relationship between nitrate concentration in exhaled breath condensate and indoor air quality - ENVIRH study - Caires, Iolanda (2014)
INTRODUCTION: Children spend a significant time of their days indoors, making it more susceptible to respiratory problems. Studies evaluating the relations between individual exposure to indoor pollutants and airways behavior are scarce. The evaluation of metabolites of nitric oxide (NO), namely nitrates (NO3-) in exhaled breath condensate (EBC), is a good biomarker of airways inflammation. Objective: Evaluate the relationship between the NO3- concentration in EBC of children attending children day care centers and total volatile organic compounds (VOCs) assessed on those institutions. METHODOLOGY: At the 2nd phase of ENVIRH project, samplings of EBC were collected, using a disposable device (RTube), from a group of children in preschool age, attending day care centers within the city of Lisbon. After sampling collection, the samples were frozen at -40°C. For the NO3- measure in the EBC, a chemiluminescence analyzer (Sievers 280i NOATM) was used. From the IAQ analyzed parameters, we highlight the PM10, VOCs, mites, fungi, bacteria, temperature and relative humidity. For data analysis, two logistic random-intercept models were used. RESULTS: We collected 100 samples of EBC in children at preschool age, with a mean age of 5.0±0.6 years. 57% of the subjects were male. The average occupancy of school rooms was 19.73±3.97 children. The NO3- in EBC mean values were 4.42±1.60 μmol and VOCs median values were 200 μg/m3 (P25-P75: 82-436 μg/m3). When analyzing the association between IAQ parameters and bronchial inflammation, it was only found an association between VOCs and NO3-: regression coefficient ( ) = 0.32, IC 95%: 0.11 to 0.53, p=0.003. Conclusion: At this study, VOCs were the only IAQ parameter significantly associated with NO3- in EBC, as biomarker of bronchial inflammation. Grant from Fundação para a Ciência e Tecnologia – ENVIRH Project PTDC/SAUESA/ 100275/2008.